Drexciya - Rittmeier, Simon 1981-; Beyer, Alexander 1973-; Hien Yeri, Josiane; Ouattara, Rodrigue (Kunsthochschule für Medien Köln, 2012)
"Drexciya was an underwater counry populated by the unborn children of pregnant African women thrown off of slave ships that had adapted to breath underwater in their mother's wombs."--Container